Koreksi kasus bimaxillary dental protrusion Disertai gigi anterior berjejal berat Dengan penjangkaran tambahan - Nofrizal, Riko (Fakultas Kedokteran Gigi Universitas Trisakti, 2024)
Background: Treatment of bimaxillary dental protrusion accompanied crowding case generally involves the extraction of four first premolar to obtain the space required to correct crowding and retraction of the anterior teeth. Additional anchorage is essential to prevent the posterior teeth from shifting during the correction process, ensuring that the space obtained from premolar extractions is fully utilized for anterior tooth retraction. Objective: This case report explain the treatment of a bimaxillary dental protrusion accompanied by severe dental crowding using additional anchorage. Case: The patient has a convex soft tissue profile, bimaxillary dental protrusion accompanied by severe crowding. The treatment included extracting all first premolars to create adequate space, followed by orthodontic repositioning of the anterior crowding in both arches. Supplementary anchorage was applied during the anterior retraction phase. After 20 months of treatment, the patient showed significant improvements in occlusion and aesthetics. Conclusion: To achieve appropriate space closure after extraction in accordance with the treatment plan, a correct strategy for controlling anchorage is required.